Pengaruh Konsentrasi Cocamide Dea Sebagai Surfaktan Pada Pembuatan Sampo Ekstrak Daun Alamanda - Agnes Berta Nasmety; Kharisma Ardea Pramest; Ira Zahara Septiani - Politeknik Katolik Mangunwijaya (Indonesian Journal on Medical Science, 2019)
Abstract: Alamanda leaf (Allamanda cathartica) in the form of extract with a concentration of 30% has been investigated to inhibit the growth of fungal causes of dandruff that Candida albicans. Alamanda leaves extracted using maceration methods are known to contain antifungal compounds that is alkaloids, flavonoids, saponins, and tannins. The preparation that can be used as a cleanser for dandruff is shampoo. One of the important compositions in making shampoo is the surfactant. One example of a surfactant that can be used in a shampoo preparation is Cocamide DEA which has the effect of emmolient (moisturizing) and foam stabilizer (stabilizing). This research is an experimental study of one factorial Completely Randomized Design (CRD), that is Cocamide DEA concentration. The concentration of Cocamide DEA used is 4%, 6% and 8%. The physical characteristics of the tested dosage included organoleptic, pH, viscosity, and foam height measurements and anticombe activity test using Candida albicans. The test results were analyzed theoretically and statistically using the ANOVA test and the Kruskall-Wallis test which had a 95% confidence level. The results of the research on the organoleptic test of the three formula preparations for the extract of alamanda leaf extract were liquid and no sediment, brown and distinctive smell. The pH value of the formula shampoo I, II, and III in a row 5.06; 5.5 and 5.86. The viscosity test results of formulas I, II, and III were 400 cP, 1849 cP and 2844 cP. Foam height for formulas I, II and III is 4 cm, 5 cm and 6.5 cm. The antifungal activity test results showed inhibition diameters for all three formulas of 1.5 cm.Key words: alamanda leaves, shampoo, cocamide DEA, anti-dandruffÂ Abstrak: Daun alamanda (Allamanda cathartica) dalam bentuk ekstrak dengan konsentrasi 30% telah diteliti dapat menghambat pertumbuhan jamur penyebab ketombe yaitu Candida albicans. Daun alamanda yang diektraksi menggunakan metode maserasi diketahui mengandung senyawa antijamur yaitu, alkaloid, flavonoid, saponin, dan tanin. Sediaan yang dapat digunakan sebagai pembersih ketombe adalah sampo. Salah satu komposisi penting dalam pembuatan sampo adalah surfaktan. Salah satu contoh surfaktan yang dapat digunakan dalam sediaan sampo adalah Cocamide DEA yang memiliki efek emmolient (melembabkan) dan foam stabilizer (menstabilkan). Penelitian ini merupakan penelitian eksperimental Rancangan Acak Lengkap (RAL) satu faktorial yaitu konsentrasi Cocamide DEA. Konsentrasi Cocamide DEA yang digunakan sebesar 4%, 6% dan 8%. Karakteristik fisik sediaan yang diuji meliputi organoleptis, pH, viskositas, dan pengukuran tinggi busa serta uji aktivitas antiketombe menggunakan jamur Candida albicans. Hasil pengujian di analisis secara teoritis dan statistik menggunakan uji Anova dan uji Kruskall-Wallis yang memiliki taraf kepercayaan 95%. Hasil penelitian pada uji organoleptis ketiga formula sediaan sampo ekstrak daun alamanda berbentuk cairan dan tidak ada endapan, berwarna coklat serta berbau khas. Nilai pH sediaan sampo formula I, II, dan III berturut-turut 5,06; 5,5 dan 5,86. Hasil uji viskositas formula I, II, dan III yaitu sebesar 400 cP, 1849 cP dan 2844 cP. Tinggi busa untuk formula I, II dan III yaitu 4 cm, 5 cm dan 6,5 cm. Hasil uji aktivitas antijamur menunjukkan diameter penghambatan untuk ketiga formula sebesar 1,5 cm.Kata kunci: daun alamanda, sampo, cocamide DEA, antiketombe